2022
DOI: 10.1002/nau.24984
|View full text |Cite|
|
Sign up to set email alerts
|

Biofeedback‐assisted pelvic floor muscle training and pelvic electrical stimulation in women with overactive bladder: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Objective This meta‐analysis aims to compare biofeedback‐assisted pelvic muscle floor training (PFMT) and pelvic electrical stimulation (ES) as an intervention group, with PFMT or bladder training (BT) as the control group, in women with an overactive bladder (OAB). Method PubMed, Cochrane, CINAHL, EMBASE, and Scopus were systematically searched for randomized controlled trials (RCTs) published up to November 2021. The RCTs were screened for our eligibility criteria and quality was evaluated using the Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…36 A metaanalysis looking at the effect of PFMT on OAB found that pelvic electrical stimulation resulted in the greatest improvement in urinary frequency, urgency, and incontinence when compared with PFMT with biofeedback. 37…”
Section: Behavioral Dietary Changes and Pelvic Floor Muscle Therapy F...mentioning
confidence: 99%
See 1 more Smart Citation
“…36 A metaanalysis looking at the effect of PFMT on OAB found that pelvic electrical stimulation resulted in the greatest improvement in urinary frequency, urgency, and incontinence when compared with PFMT with biofeedback. 37…”
Section: Behavioral Dietary Changes and Pelvic Floor Muscle Therapy F...mentioning
confidence: 99%
“…Because PFMT regimens are heterogeneous, it is difficult to compare data across trials, but there is little risk and some benefit 36 . A meta-analysis looking at the effect of PFMT on OAB found that pelvic electrical stimulation resulted in the greatest improvement in urinary frequency, urgency, and incontinence when compared with PFMT with biofeedback 37 …”
Section: Management Of Genital and Sexual Problems Of Gsm— Vulvovagin...mentioning
confidence: 99%
“…In the article by Leonardo et al, 1 we have noticed two errors related to the data shown in the Abstract section.…”
mentioning
confidence: 91%